Psychosexual Interventions for Childhood Sexual Abuse Survivors: A Narrative Review in Obstetric and Gynecological Care - Mochamad Rizkar Arev Sukarsa; Alce Everdien; Ahmad Ikbal Purnawarman; Immanuel Bachtiar Parlindungan; Jacklyn Yosefin Gracia Lubis; Marsha Marvella; Wynona Monica Ellsa Wiharja (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: To evaluate the effectiveness of psychosexual interventions in improving sexual function and related psychological outcomes among women with a history of childhood sexual abuse, and to explore their clinical relevance and applicability in obstetric and gynecological care settings.Methods: A narrative review of literature from PubMed and ScienceDirect, published through February 2026, was conducted. Included studies involved adult women with a history of childhood sexual abuse who received psychosexual interventions and reported sexual or psychological outcomes. Non-primary studies and those failing to meet inclusion criteria were excluded.Results: Eight studies discussing psychosexual interventions were included, mainly comprising of cognitive-behavioral approaches, mindfulness-based therapy, and expressive writing, demonstrated improvements in sexual function, particularly desire and arousal, and reductions in sexual distress. Trauma-focused therapies, including TF-CBT, EMDR, and CPT, primarily reduced PTSD and related psychological symptoms, resulting in indirect effects on sexual health. This review also summarizes main principles of psychosexual interventions relevant for clinical application. Conclusion: Childhood sexual abuse has long-term effects on sexual functioning across multiple domains. Integrating trauma-focused and psychosexual interventions is crucial for supporting recovery and optimizing sexual health outcomes. In clinical practice, this includes routine screening, tailored counseling that accommodates cognitive and emotional vulnerabilities, and the application of trauma-informed and human rights-based care. Future research is warranted to strengthen these clinical applications.Intervensi Psikoseksual pada Penyintas Kekerasan Seksual Anak: Tinjauan Naratif dalam Praktik Obstetri dan GinekologiAbstrakTujuan: Untuk mengevaluasi efektivitas intervensi psikoseksual dalam meningkatkan fungsi seksual dan luaran psikologis terkait pada perempuan dengan riwayat kekerasan seksual pada masa kanak-kanak, serta mengeksplorasi relevansi dan aplikasinya dalam praktik obstetri dan ginekologi.Metode: Tinjauan naratif dilakukan menggunakan PubMed dan ScienceDirect hingga Februari 2026. Studi yang melibatkan perempuan dewasa dengan riwayat kekerasan seksual pada masa kanak-kanak yang menerima intervensi psikoseksual dan melaporkan luaran seksual atau psikologis disertakan. Studi non-primer dan yang tidak memenuhi kriteria tidak diinklusikanHasil: Sebanyak delapan studi yang membahas intervensi psikoseksual disertakan, terdiri dari terapi berbasis mindfulness, expressive writing, dan pendekatan kognitif-perilaku menunjukkan perbaikan fungsi seksual, terutama pada aspek hasrat, gairah, dan distres seksual. Terapi berfokus trauma seperti TF-CBT, EMDR, dan CPT terutama menurunkan gejala PTSD dan gangguan psikologis terkait, dengan efek tidak langsung terhadap kesehatan seksual. Tinjauan ini juga merangkum prinsip-prinsip utama psikoseksual yang relevan bagi praktik klinis.Kesimpulan: Kekerasan seksual pada masa kanak-kanak berdampak jangka panjang terhadap fungsi seksual di berbagai domain. Integrasi terapi berfokus trauma dan intervensi psikoseksual penting untuk mendukung pemulihan dan meningkatkan kesehatan seksual. Dalam praktik klinis, hal ini mencakup skrining rutin, konseling yang disesuaikan dengan keterbatasan kognitif dan emosional, serta penerapan pendekatan berbasis trauma dan hak asasi manusia. Penelitian berkualitas tinggi masih diperlukan untuk memperkuat aplikasi klinis.